A prototype of high-performance two-electron non-aqueous organic redox flow battery operated at −40 °C. Issue 46 (14th November 2022) - Liang, Zhiming; Jha, Rahul Kant; Suduwella, Thilini Malsha; Attanayake, N. Harsha; Wang, Yangyang; Zhang, Wei; Cao, Chuntian; Kaur, Aman Preet; Landon, James; Odom, Susan A.
Abstract : Non-aqueous redox flow batteries which can be operated under subzero temperature are significant for applications in cold regions. Abstract : Redox flow batteries (RFBs) which can be operated under subzero temperature are significant for applications in cold regions, however, very few RFBs have been reported for use below −20 °C. Problems with active materials, such as low solubility, poor electrochemical stability, and high viscosity are the major difficulties to overcome. Herein, we report a prototype of ultra-low temperature (−40 °C) non-aqueous RFB, using two-electron glycolated phenothiazine and viologen as posolyte and negolyte, respectively, which successfully completed 100 cycles at 15 mA cm −2 . The cell which was assembled with 0.1 mol L −1 active materials exhibited a theoretical voltage of 1.9 V, an average discharge volumetric capacity of 3.2 A h L −1, and ca. 78% capacity retention over 100 cycles. Increasing the active material concentration to 0.25 mol L −1, the discharge volumetric capacity reached ca. 8.5 A h L −1 . This marks for the first time a non-aqueous RFB has been long-term cycled at a high current density at ultra-low temperature.